Spaces for highly mobile people emerging practices of mobility in Italy - Vendemmia, Bruna (Transport and mobility, 2021)
This book explores how emerging mobility practices have transformed spaces in order to fit the needs of highly mobile people, as well as the changing relationship between people and territory. It establishes an interdisciplinary and a multiscalar approach to mobility analysis and mobility design through the application of a mobile method of research. Drawing on mobile people in Italy, the book highlights how influential movers appropriate and configure space for their own needs, centring their activities on continuous but distant places and configuring territories with uncertain and evolving limits. This change of perspective allows us to redefine the concept of mobility space, including all the spaces that support the development of emerging mobility practices. It also encourages new perspectives on the way in which the relationship between the individual and territory is evolving into a less sedentary way of inhabiting space. This book will be of interest to architects, urban scientists and sociologists, as well as postgraduate students who are interested in understanding how mobilities are transforming contemporary cities and territories